Lei de cotas no Brasil: garante a entrada e conclusão dos alunos com deficiência nas universidades? - Silva, Pamella Maria Nogueira Moreira (2024)
Even though people with disabilities (PwDs) represent a sizable portion of the population, they encounter obstacles and discrimination when trying to exercise their fundamental rights. Therefore, it becomes crucial to implement policies that promote the inclusion of this group in society. This study aims to investigate the impact of Law No. 13,409, enacted on December 28, 2016, on the total enrollment and graduation rates of people with disabilities in higher education. This law deals with the reservation of seats for PwDs in Federal Public Higher Education Institutions (IFES). This study adds to the existing literature in education by aiming to assess the impact of this Law, considering the limited number of empirical studies examining public policies targeted at PwDs. To achieve the stated objectives, we utilized enrollment and graduated data from the Higher Education Census, education quality indicators from INEP and management indicators from the TCU Report covering the period from 2013 to 2022. We obtained causal estimates at the level of Institutions and Courses using the Two-Way Fixed Effects (TWFE) model. We conducted robustness tests, including placebo tests and the exclusion of universities with internal policies concerning Persons with Disabilities (PwDs). Additionally, we performed an analysis of heterogeneous effects by Brazilian regions, considering institutional data, and by Area of Knowledge, based on Course information. The main results show positive and significant effects of the Law on total enrollment in higher education, both for IFES observation units and for courses, demonstrating the effectiveness of the Law. These results maintained their robustness when undergoing the analyzed tests, including the parallel trends test. However, the same cannot be affirmed regarding the Law's effect on total graduates. Heterogeneous effects by region were significant and positive, except for the Central-West region. Among courses by area of knowledge, only Linguistics, Letters and Arts, Exact and Earth Sciences, Health Sciences, and Agricultural Sciences followed the main model's results in total enrollment of students with disabilities.